Association constants of dibenzo[3n+2]crown-n ethers using steady-state fluorescence spectroscopy - Tuncer, H; Erk, C (Elsevier, 2005)
The steady-state fluorescence spectra of cation complexes of fluorophore macrocyclic ethers have been studied for the estimation of 1: 1 association constants, and perchlorate salts of Li+, Na+, K+ Rb+ and Pb2+ complexing with dibenzo[23]crown-9, dibenzo[26]crown-10, and sym-dibenzo[26]crown-10, were investigated. The fluorescence emission maximum of the free and the various ligand/cation mixtures of complexed crown ethers were measured at room temperature in AN. The concentrations of chromophore crown ether were obtained from nonlinear calibration plots. The 1:1 stoichiometry of association constants (K-ass) were calculated using the equation, 1/K-ass[L-o] =(1 - nP)(n)(1 - m)(m)/P with linear best fit of plots depending on 1/[L-o] where P = P-C/[1 + (m - 1)P-C] and P-C is the mole fraction of n/m ratio of the complexed ligand. The association constants of cations, K-ass, displayed the cation selectivities depending on the cation radii and the macrocyclic ether size. and Pb+ was found to give the strongest association with such crown ethers. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: dibenzocrown ethers; cation association constant; fluorescence spectroscopy